TEACHERS' STRATEGIES IN DEVELOPING STUDENTS' CHARACTER IN SOCIAL STUDIES SUBJECTS AT SDN 12 TERNATE CITY: STRATEGI GURU DALAM MENGEMBANGKAN KARAKTER SISWA PADA MATA PELAJARAN IPS DI SDN 12 KOTA TERNATE - Ansi; Mohtar Kamisi; Andi Tenri Pada Agustang (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe teachers' strategies in developing student character in social studies subjects at SDN 12 Ternate City. The background of this research departs from the importance of character education in social studies learning which not only emphasizes the aspect of knowledge, but also the formation of students' social attitudes and behaviors. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that social studies teachers at SDN 12 Ternate City apply several character development strategies, including: (1) integration of character values such as discipline, responsibility, tolerance, and cooperation in each learning material; (2) the use of discussion-based learning methods, case studies, and group work to foster social attitudes; (3) setting an example through teachers' behavior in daily interactions; and (4) giving appreciation and positive reinforcement to encourage character behavior. The conclusion of this study is that teachers' strategies in developing character in social studies learning have been effective, although there are still obstacles such as lack of supporting facilities and variations in learning methods. This research is expected to be a reference for schools and teachers in improving the quality of character education at the elementary school level.